The relationship between family intimacy and relapse tendency among people who use drugs: a moderated mediation model - Xiaoqing Zeng; Mengyao Lu; Meirong Chen (BMC, 2021)
Abstract Background Drug addiction is difficult to overcome. The relapse rate is high, and the negative impact on individuals, families and society is severe, therefore exploring social psychological mechanisms to reduce relapse has very important theoretical and practical value. However, the underlying mechanism by which the interaction between family and individual factors influences the tendency to relapse remain unclear. Thus, the purpose of this paper is to discuss the relationship between family intimacy and relapse tendency of people who use drugs, as well as the mediating effect of psychological capital and the role of self-efficacy in it. Methods A total of 817 male who use drugs were investigated via the Family Intimacy and Adaptability Scale, General Self-Efficacy Scale, Positive Psychological Capital Questionnaire and Relapse Tendency Questionnaire. Using Hayes's process macro carried out moderated mediation analysis. Results (1) The average family intimacy score of people who use drugs was low. (2) Family intimacy negatively predicted relapse tendency in people who use drugs. (3) Psychological capital mediated the relationship between family intimacy and relapse tendency. (4) The first half of the indirect effect of family intimacy on relapse tendency was regulated by self-efficacy, compared with the low level of self-efficacy, the psychological capital level with high self-efficacy is higher. Conclusion The results of this study suggest that the intimacy between the people who use drugs and their family members should be improved, and the rehabilitation center should take various measures to enhance the psychological capital level and the level of self-efficacy of the people who use drugs, which will be helpful to reduce their relapse tendency.